Investigation On Oxidation Behavior of Nuclear Graphite IG-110 At Elevated Temperature - Herlina; Abu Khalid Rivai; Sigit Khalid Rivai (BRIN Publishing (Penerbit BRIN), 2023)
IG-110 is one of nuclear graphite types for high temperature gas cooled reactor. One of the issues of the graphite in the reactor system is the interaction with air or/and water which can reduce the integrity of the material. In this study, the sample of IG-110 has been tested at high temperature in an air environment. The oxidation test was done using a magnetic suspension balance to analyze the changes in weight with direct monitoring. The test was carried out at a temperature of 630°C. Morphological and microstructural analysis were observed and tested using scanning electron microscope (SEM) and X-ray diffractometer (XRD). The oxidation rate of the sample was relatively low. Rougher sheets shape, larger pores, and slight cracks were observed for the tested sample which indicate the traces of oxidation of the samples with no any critical damage occurred in the sample. Lattice parameters, density, crystal size, and d-space of the sample after oxidation test slightly change, which show the reversible characteristic of the sample from the temperature viewpoint.